As contradições presentes no currículo e nos projetos políticos pedagógicos das escolas do campo de Limeira/SP: uma análise a partir da Pedagogia histórico-crítica - Jurgensen, Karina Yara (2025)
This research investigates the implementation of Historical-Critical Pedagogy (HCP) in the curriculum of the municipal education network of Limeira-SP and its relationship with the Political Pedagogical Projects (PPPs) of rural schools, considering the specificities of this educational context. The study is based on the assumption that, in a scenario marked by neoliberal policies in education, the Common National Curriculum Base (BNCC), guided by competencies and skills, significantly influences teacher training, teaching materials, and standardized assessments—elements that do not align with the principles of HCP. To analyze this issue, a qualitative approach was adopted, combining a literature review (theses and dissertations on HCP, curriculum, and Rural Education) and document analysis (Limeira’s municipal curriculum and the PPPs of rural schools). The results revealed that: (1) the municipal curriculum does not incorporate the particularities of Rural Education, reflecting a disconnect with the needs of this population; (2) the BNCC, as a hegemonic policy, subordinates pedagogical practice to meritocratic logics, limiting the effective implementation of HCP; and (3) while the PPPs make occasional references to HCP and Rural Education, they lack theoretical depth or concrete proposals. It is concluded that, although HCP is the official pedagogical approach of the municipal network, its materialization faces structural challenges, such as the predominance of the BNCC and the lack of specific curricular guidelines for Rural Education. Therefore, it would be pertinent to revise the municipal curriculum to include the specificities of Rural Education, alongside critical continuing teacher training, aiming to strengthen HCP as a transformative alternative to the neoliberal educational model.